Structure and Meaning of the Dugale Asu Maring Menungsa Tegalan Dialect Poetry by Atmo Tan Sidik - Muslim, Tiar; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Poetry Dugale Asu Maring Menungsa is a poem written using the Javanese language Tegalan dialect. The Poetry of Dugale Asu Maring Menungsa reflects Indonesian culture, especially the people of Tegal and Brebes. The purpose of this research is to describe the physical and mental structure and to describe the meaning in Atmo Tan Sidik's Dugale Asu Maring Menungsa Poem. This study uses a semiotic structural approach. Data collection in this study used the first level reading techniques, namely heuristics and literature study. The data analysis technique was carried out by means of hermeneutical reading. The results of this study indicate that the Dugale Asu Maring Menungsa Poetry has two structures, namely physical and mental structures. Figurative language is the most dominant physical structure used in Dugale Asu Maring Menungsa's Poetry compared to diction, images, concrete words, versification and typography. The figurative language used in Dugale Asu Maring Menungsa's Poetry is personification and sarcasm. The theme contained in The Dugale Asu Maring Menungsa Poetry is a social theme. The tone used is the tone of satire. The meaning of Dugale Asu Maring Menungsa's Poetry, which describes the anger of a dog towards humans who always blame and call it when they get a social problem